2018
DOI: 10.1097/coc.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PD-L1 and PD-1 Expression and CD8+ Tumor-infiltrating Lymphocyte in Epstein-Barr Virus-associated Nasopharyngeal Carcinoma

Abstract: Approximately 70% of EBV-positive NPC expressed PD-L1, but this did not correlate with patient survival or clinicopathologic features. The findings of this study represent the immune biomarker profile of confirmed EBV-associated NPC in an endemic region. Since the current clinical development of immune checkpoint inhibitor for NPC is mostly focusing on an EBV-associated tumor, differences in immune biomarker profiles and EBV status of endemic and nonendemic regions should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…Our data show a positive expression of PD-L1 in 70% of cases, which is consistent with previous reports [12,17,18]. The correlation between PD-L1 expression and better prognosis is consistent with Zhu et al [14] and Lee et al [18] who found PD-L1 to correlate with favorable prognosis in NPC.…”
Section: Discussionsupporting
confidence: 93%
“…Our data show a positive expression of PD-L1 in 70% of cases, which is consistent with previous reports [12,17,18]. The correlation between PD-L1 expression and better prognosis is consistent with Zhu et al [14] and Lee et al [18] who found PD-L1 to correlate with favorable prognosis in NPC.…”
Section: Discussionsupporting
confidence: 93%
“…Previous clinical studies have demonstrated that NPC is densely infiltrated by T cells [45], where the presence of more TIL, particularly CD3 + T cells, was associated with favorable outcomes [46,47]. In our model, TIL was detected in the humanized mice, and the percentage of intratumoral T cells was lower than those in circulation and spleen.…”
Section: Discussionmentioning
confidence: 58%
“…38 PD-1 expression in CD8+ cells has been associated with the selective suppression of cytotoxic lymphocytes in EBV positive nasopharyngeal carcinoma. 43 On the other hand, the PD-1+ TILs have also been described to lack Tim-3 expression in papilloma virus positive cancers, and thus possibly representing activated T-cells. 44 Emerging evidence in EBV-related malignancies indicates that the virus possesses the ability to actively shape the tumor microenvironment, and favours its escape from anti-tumor immune responses through a variety of complex mechanisms.…”
Section: Discussionmentioning
confidence: 99%